1998
DOI: 10.1590/s0100-879x1998000800007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of the microalga Spirulina maxima

Abstract: Spirulina maxima, which is used as a food additive, is a microalga rich in protein and other essential nutrients. Spirulina contains phenolic acids, tocopherols and ß-carotene which are known to exhibit antioxidant properties. The aim of the present study was to evaluate the antioxidant capacity of a Spirulina extract. The antioxidant activity of a methanolic extract of Spirulina was determined in vitro and in vivo. The in vitro antioxidant capacity was tested on a brain homogenate incubated with and without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
189
0
22

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(217 citation statements)
references
References 14 publications
6
189
0
22
Order By: Relevance
“…The antioxidant potentials of the extracts obtained from S. platensis grown under these conditions were 29 and 35% for the medium containing 1.875 g.L -1 and 2.5 g.L -1 of sodium nitrate (Table 2), respectively. According to Miranda et al (1998), the main phenolic compounds found in Spirulina were salicylic, trans-cinnamic, synaptic, chlorogenic, quimic and caffeic acids. However, the metabolic pathways for the formation of these compounds in cyanobacteria and their importance were still unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant potentials of the extracts obtained from S. platensis grown under these conditions were 29 and 35% for the medium containing 1.875 g.L -1 and 2.5 g.L -1 of sodium nitrate (Table 2), respectively. According to Miranda et al (1998), the main phenolic compounds found in Spirulina were salicylic, trans-cinnamic, synaptic, chlorogenic, quimic and caffeic acids. However, the metabolic pathways for the formation of these compounds in cyanobacteria and their importance were still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds have been extensively studied for their antioxidant properties not only in fruits and vegetables (Amaral et al, 1995;Frankel et al, 1995;Yen and Chen, 1995;Yoshino and Murakami, 1998;Duval and Shetty, 2001) but also in cyanobacteria. For example, Miranda et al (1998) studied the antioxidant activity of carotenoids, phenolics and tocopherols extracted from S.maxima and found that the phenolic compounds responsible for the antioxidant properties of the S. maxima extracts were organic acids (caffeic, chlorogenic, quimic, salicylic, synaptic and trans-cinnamic) which acted individually or synergistically, while Estrada et al (2001) demonstrated the antioxidant activity of the phycobiliproteins phycocyanin and alophycocyanin present in Spirulina biomass. The aim of this work was to investigate the influence of the temperature and nitrogen concentration on the production of phenolics by Arthospira platensis and to assess the antioxidant activity of these phenolics based on their capacity to prevent peroxidase-induced browning of guayacol.…”
Section: Introductionmentioning
confidence: 99%
“…platensis is rich in polyunsaturated fatty acids and phycocyanin [22][23][24] . Some researchers [31,50,51] reported that the polyunsaturated fatty acids in S. platensis help to reduce serum lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…platensis is a microscopic filamentous alga, which contains several vitamins, especially vitamin B 12 and provitamin A (beta-carotene). Also, it is rich in polyunsaturated fatty acids, phycocyanin [22,23] and phenolic compounds [24] . Over the years, many dietary supplements of S. platensis have a widespread use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation